(3MOGFb GdJeGe aj GdcdGe Ydi eG jJYdb HGdMeGes - (3GdchcHGfj , CMeO Hf eMeO Hf GdMSjf,J (B1181 (3g` s ((3Ydj Hf CMeO Hf QGLM Hf SYjO s)
(3ChdgG (B:s
(3EPG cGf GdMeGe ef GdfYje GdeMOK ajfG, aWGdeG CUM GdCLSGO aGdMeO ddg Ydi fYeI efGg MOjKI, MeOG jSJZQb ef GdeMOK GdeWfH MOjKg bGd GdMbjQ dG jNaj Cf fYeI GdMeGe GdehLHI ddTcQ s
(3BNQgG (B:s
(3CbdgG fYeI GdMeGe hgj fYeI LfI aj fGQ hcfR eMJGL JeGRLg fThg GdaQL efg eGdG JeGR Hg fThI OQge hOjfGQ dG RdJ aj fYje hdGHQMJ fGFdG dfYje GdLfI ef GdLMje s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B243s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B257 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs